A PROPOSAL FOR INTEGRATING DATA OF LAND REGISTRY AND URBAN CADASTRE - Paiva, Caio dos Anjos; Antunes, Alzir Felippe Buffara; Camboim, Silvana (Boletim de Ciências Geodésicas, 2018)
It is noted a lack of integration between information of the Land Registration (LR) and of the Urban Cadastre in various Brazilian municipalities. Due to the lack of regulations at national level that define a conceptual model to organize the data from different entities, the design of integration systems geared to such a purpose is made difficult. Therefore, this study aims at developing an exchange prototype of the mentioned data from a previous research conducted by Paiva et al. (2016), concerning the modeling of the data resultant from LR and Urban Cadastre. To this end, we used the existing situation in the municipality of São José dos Pinhais, Curitiba metropolitan region, as a case study. There, the exchange of information between both entities is similar to that of many Brazilian municipalities. A conceptual model was generated and used to create an object-relational database, which then was used to develop an administrative and geospatial data consultation and editing prototype, based on technologies known as open-source. The use of such programs allowed us to verify the reproducibility possibility of the computational solutions referred herein to other cities with different economic situations.